Marine Shaft Steels (AISI 4140 and AISI 5120) Predicted Fracture Toughness by FE Simulation - Goran VUKELIC; Josip BRNIC (Medžiagotyra, 2017)
Optimal selection of material can be considered as one of the most critical steps in engineering design process. That is especially emphasized when dealing with constructions that operate in marine environment; high stresses and harsh operating conditions assert the importance of proper material characterization before its selection. This paper presents comparison of two types of steel usually used in marine shaft manufacturing, chromium-molybdenum steel AISI 4140 and chromium low-alloy steel AISI 5120. Comparison was made using numerically determined J-integral, an important fracture mechanics parameter. J-integral values are determined numerically using finite element (FE) stress analysis results of compact tensile (CT) and single-edge notched bend (SENB) type specimens usually used in standardized J-integral experimental procedures. Obtained J values are plotted versus specimen crack growth values (Δa) for different specimen geometries (a/W). Higher resulting values of J-integral for AISI 5120 than AISI 4140 can be noticed. Also, higher a/W ratios correspond to lower J-integral values of materials and vice versa. In addition to that, J-integral values obtained by using FE model of CT specimen give somewhat conservative results when compared with ones obtained by FE model of SENB specimen. Although this procedure differs from experimental analysis, results can be used a suitable fracture parameter value in fracture toughness assessment. DOI: http://dx.doi.org/10.5755/j01.ms.23.1.13823